Netter atlas of human anatomy classic regional approach - Netter, Frank H. (Elsevier, 2023)
For clinical professionals or students who are learning anatomy, participating in a dissection lab, sharing anatomy knowledge with patients, or refreshing their anatomy knowledge, the Netter Atlas of Human Anatomy illustrates the body, region by region, in clear, brilliant detail from a clinician's perspective. Unique among anatomy atlases, it contains illustrations that emphasize anatomic relationships that are most important to the clinician in training and practice. Illustrated by clinicians, for clinicians, it contains more than 550 exquisite plates plus dozens of carefully selected radiologic images for common views. This Professional hardcover edition includes access to a downloadable imagebank for personal use.